1994
DOI: 10.1063/1.111636
|View full text |Cite
|
Sign up to set email alerts
|

Resistance switching in indium phosphide using hydrogen passivation of acceptors

Abstract: Articles you may be interested inUse of dipole doping to suppress switching in indium phosphide double heterojunction bipolar transistors Absolute photoionization cross sections of the acceptor state level of chromium in indium phosphide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…This is consistent with the results obtained by Svendsen et al [36]. In addition, Balasubramanian et al [34] reported that plasma exposure with a power of 0.5 W cm À2 for 60 min leads to surface damage and the formation of In droplets as P is lost as PH 3 in the case of InP (melting temperature of 1062 C). According to EDX analysis, the phosphorus amount remained unchanged when the NieP coatings were treated with hydrogen plasma at 600 W. Thus, the phosphorous did not sublimate into gas under 600 W hydrogen plasma treatment for 1 min in this study.…”
Section: Power Of Hydrogen Plasmasupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with the results obtained by Svendsen et al [36]. In addition, Balasubramanian et al [34] reported that plasma exposure with a power of 0.5 W cm À2 for 60 min leads to surface damage and the formation of In droplets as P is lost as PH 3 in the case of InP (melting temperature of 1062 C). According to EDX analysis, the phosphorus amount remained unchanged when the NieP coatings were treated with hydrogen plasma at 600 W. Thus, the phosphorous did not sublimate into gas under 600 W hydrogen plasma treatment for 1 min in this study.…”
Section: Power Of Hydrogen Plasmasupporting
confidence: 91%
“…Although the hydrogen atom has a relatively small mass, resulting in a small degree of the bombardment effect, if the hydrogen atom or ion can react with the materials to form volatile hydride compounds, this indicates that the materials were etched. Thus, hydrogen plasma can effectively etch carbon-related materials and a number of semiconductors (e.g., Si, GaAs, and InP) [34]. When hydrogen plasma is used to process the materials, the temperature of the materials increases with the inelastic collision of hydrogen molecules, atoms, or ions, and the oxide of the materials is reduced into metal because of the reaction of oxygen in the oxide and hydrogen radials.…”
Section: The Effect Of Hydrogen Plasma Treatmentmentioning
confidence: 99%
“…[15][16][17][18]23,24 A rigid molecule is defined as one in which the barriers between its conformers are insuperable and there are no observable tunneling splittings. [26][27][28][29][30][31][32][33][34][35] In the present study, the Fujita combinatorial enumeration tables of the f-NRG of 2,4-dimethybenzene (see Fig. Due to this deformability, non-rigid molecules exhibit some interesting properties of in-92 MOGHANI, SEDEH and SOROUHESH tramolecular dynamics which can be studied more easily by resorting to group theory.…”
Section: Introductionmentioning
confidence: 99%
“…9,12 For this reason, a study of the thermal stability of dopant-hydrogen complexes assumes importance. These studies are also required for making devices based on neutralization effects caused by hydrogenation [14][15][16] and for deciding the temperature range of safe operation of such devices.…”
Section: Introductionmentioning
confidence: 99%
“…͑6͒. The passivation depth is taken as the depth at which the active acceptor concentration is 1.3ϫ1016 cm Ϫ3 and is determined from the active acceptor concentration profiles. The solid lines represent the least squares fit to the experimental data in the linear portion of the plot.…”
mentioning
confidence: 99%